IMPLEMENTATION OF UNLIMITED DENTAL SUPERVISION - Teti Sutriani; Montisa Mariana; Irma Maulida (International Peneliti Ekonomi, Sosial dan Teknologi, 2022)
Since the beginning of January 2013, the number of registered dental professionals is ± 75,000. There are still many dental artisan practices indicating that our society is interested in dental services. The legal basis for dental work has been regulated by the government, in this case the Ministry of Health issued Permenkes No. 53/DPK/1/K/1969 and Permenkes No. 339/MENKES/PER /V/1989 on dental work. The regulation regulates the authority, prohibition and licensing of dental artisans.In Indonesia, dental technicians who carry out dental work are required to register with the district/city government or the local district/city health office to obtain a dental technician's license. The dental technician's license is valid for two years and can be extended as long as it meets the requirements.Research with approach methodnormative juridical, namely the method of collecting data by conducting a literature review associated with problems as mentioned above. Based on the results of the research, dentists who carry out dental work without having a dental technician's license and work outside their authority can be subject to sanctions based on the Medical Practice Act article 73 paragraph (2). the person concerned is subject to sanctions. If the patient feels aggrieved by the services provided by the dental artisan, the patient can claim compensation. The Cirebon City Health Office has not carried out periodic supervision of dental artisans in the city of Cirebon. This is because there are obstacles in the workforce (HR) to carry out such supervision.